Environmental and economic implications of alternative cruise ship pathways in Bermuda. (November 2016) - Lester, Sarah E.; White, Crow; Mayall, Kevin; Walter, Ryan K.
Abstract: As the cruise ship industry moves towards ever larger vessels, many tourist destinations are faced with dilemmas about how to accommodate the latest generation of ships, which require deeper and wider shipping pathways. The location of nearshore shipping channels traveled by cruise ships has important environmental and economic implications, as dredging larger lanes damages habitat, ship traffic produces sediment plumes that can smother adjacent sensitive habitats (e.g., coral reefs, seagrass beds), and dredging costs vary spatially. These environmental and economic costs should ideally be evaluated in the context of projected benefits from increased tourism. To inform decision-making on cruise ship pathway design, we evaluated tradeoffs among tourism revenue to the local economy, dredging costs, direct coral damage and sedimentation impacts to coral reefs of alternative cruise ship approach channels for the island of Bermuda. We compiled economic data on cruise tourism and dredging costs and developed a sediment particle tracking model, overlaid on maps of coral cover, to track the spread of sediment particles and resulting coral sedimentation caused by cruise ships. Using our models we compared two viable routes, if dredged, for larger ships to reach Bermuda, along with a scenario of no dredging in which the next generation of larger ships is not accommodated. Our tradeoff analysis shows that the status quo (no dredging; no larger ships) scenario performs relatively well except for the risk of a significant loss in tourism revenue. When selecting between the two channel upgrade scenarios, the south channel upgrade is preferable if dredged material can be reused, thereby recouping dredging costs; otherwise, there is a strong tradeoff between upgrade costs and coral sedimentation. While developed with data layers and inputs specific to Bermuda, this analytical approach could easily be configured to other locations facing similar spatial planning decisions about whether and where to allow pathways for larger cruise ships. Highlights: Cruise ships are increasing in size, requiring deeper and wider shipping lanes. Tradeoffs were evaluated for upgrading alternative cruise ship channels in Bermuda. Tourism revenue, dredging costs, and coral damage and sedimentation were considered. Tradeoffs exist between upgrade costs and coral smothering unless spoil is reused. Analytical approach applies to other coastal destinations presented with mega-ships.